2016
DOI: 10.1111/jocn.13469
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self‐efficacy and quality of life in patients with temporary enterostomy: a cross‐sectional survey

Abstract: Promoting stoma-related self-efficacy in patients with temporary enterostomy may improve their quality of life. Healthcare providers should focus on quality of life in those either with temporary loop ileostomy or entirely self-funded for medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 29 publications
2
20
2
10
Order By: Relevance
“…This is consistent with study from Iran and China where 83.33% patients reported changing or leaving their jobs after enterostomies. 8,9 Effect of stoma creation on marital status was negligible. There were no incidences of divorce or separation post stoma creation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is consistent with study from Iran and China where 83.33% patients reported changing or leaving their jobs after enterostomies. 8,9 Effect of stoma creation on marital status was negligible. There were no incidences of divorce or separation post stoma creation.…”
Section: Discussionmentioning
confidence: 96%
“…8 A similar study in 2011 by Iranian Ostomy Society, mean age was 53.5 years. 9 This difference in age distribution can be explained by the attributes of sample, as most of these studies focused mainly on purely permanent stoma or sometimes on purely temporary stomas. But our study included both permanent and temporary stomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐efficacy has been considered in the literature to be a factor associated with positive health outcomes after an ostomy (Su et al., 2016, 2017). However, few studies have identified the association between self‐care self‐efficacy and ostomy self‐care.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings are reported in a recent study of ostomy supplies and payment method as significant factor for the QOL study on temporary enterostomy patients in five hospitals in Guangdong Province, China and the Veterans Affairs Ostomy Health-Related QOL Study in USA. 20,21 Development of stoma care in China has been mainly confined to hospital based inpatients and outpatients services which need to expand in to the community. Integration of standardized multidisciplinary team including specialized stoma nurses, clinicians, and psychotherapists from the early period of diagnosis and treatment plan is important to improve the quality of colorectal cancer treatment.…”
Section: Resultsmentioning
confidence: 99%